2018
DOI: 10.1080/03098265.2018.1514489
|View full text |Cite
|
Sign up to set email alerts
|

Student housing as a learning space

Abstract: This paper is an initial exploration of the significance of students' accommodation as spaces for learning. In interviews, students of Geography and Planning discuss the spatiality of studying, and how their student housing features in this. The diversity of student living and studying emerges clearly. Yet there are some commonalities, notably the significance of the materiality of accommodation as a factor that shapes and is in turn shaped by students' agency. Their accounts underline the ways they seek to sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 27 publications
0
22
0
Order By: Relevance
“…Gobbi and Rovea [34] argue, in this context, that spatial changes due to distance learning go hand in hand with a reduction of the university as a joint (inter)actional and socio-material space to scattered digital spaces on one or more devices. These devices are embedded in the everyday living environments, the home spaces, of the students [35], which is why students experience a new kind of homemaking. Furthermore, while the home space, with various functionalities already intersecting in it, becomes the (new) individual educational and learning space, this does not mean that students find themselves alone in this new assemblage.…”
Section: Effects Of the Covid-19 Pandemic On The Spatiality Of University Students' Education And Learningmentioning
confidence: 99%
See 1 more Smart Citation
“…Gobbi and Rovea [34] argue, in this context, that spatial changes due to distance learning go hand in hand with a reduction of the university as a joint (inter)actional and socio-material space to scattered digital spaces on one or more devices. These devices are embedded in the everyday living environments, the home spaces, of the students [35], which is why students experience a new kind of homemaking. Furthermore, while the home space, with various functionalities already intersecting in it, becomes the (new) individual educational and learning space, this does not mean that students find themselves alone in this new assemblage.…”
Section: Effects Of the Covid-19 Pandemic On The Spatiality Of University Students' Education And Learningmentioning
confidence: 99%
“…Furthermore, while the home space, with various functionalities already intersecting in it, becomes the (new) individual educational and learning space, this does not mean that students find themselves alone in this new assemblage. Rather, they are embedded in altered relational networks [36], in which people, objects, and routines remain closely connected [35] and sociality, including the collective of the university, is maintained by digital means [37]. Following Bork-Hüffer et al [38], one can speak of cON/FFlating educational and learning spaces that are simultaneously shaped by entangled socio-material and techno-social relations and spaces.…”
Section: Effects Of the Covid-19 Pandemic On The Spatiality Of University Students' Education And Learningmentioning
confidence: 99%
“…Authority relations are always spatial relations, and research in geography and related disciplines has analysed a wide variety of university teaching spaces, including field study visits (France and Haigh, 2018), online spaces (Lynch et al, 2008), experimental classrooms (Lambert, 2011), student housing (Card and Thomas, 2018), and much else. However, the traditional lecture theatre remains a dominant space of authority in most university courses, and needs further attention (Jamieson, 2003;Jamieson et al, 2000).…”
Section: Experiential Authority In the Lecture Theatrementioning
confidence: 99%
“…However, other year groups are of concern: one study found that subjective wellbeing decreases across three years at university (Bewick, Koutsopoulou, Miles, Slaa, & Barkham, 2010); another found that second year students had the highest level of psychiatric symptoms as measured by the General Health Questionnaire (Macaskill, 2013). In their second year, most UK students move from university halls to privately rented housing, which often involves a change of housemates (Rugg, Ford, & Burrows, 2004), and sometimes a third move occurs in the third year (Card & Thomas, 2018). This shift in accommodation, possibly with new peers, highlights that exploring the impact of housemates on wellbeing should cover the whole duration of the university experience, not just the first year.…”
Section: Introductionmentioning
confidence: 99%